Free volumes and gas transport in polymers: amine-modified epoxy resins as a case study. Issue 5 (14th January 2016) - Patil, Pushkar N.; Roilo, David; Brusa, Roberto S.; Miotello, Antonio; Aghion, Stefano; Ferragut, Rafael; Checchetto, Riccardo
Abstract : Fractional free volume and its temperature evolution evaluated using only experimental data allow describing gas diffusivity in the framework of free volume theory. Abstract : The CO2 transport process was studied in a series of amine-modified epoxy resins having different cross-linking densities but the same chemical environment for the penetrant molecules. Positron Annihilation Lifetime Spectroscopy (PALS) was used to monitor the free volume structure of the samples and experimentally evaluate their fractional free volume f h ( T ) and its temperature evolution. The analysis of the free volume hole size distribution showed that all the holes have a size large enough to accommodate the penetrant molecules at temperatures T above the glass transition temperature T g . The measured gas diffusion constants at T > T g have been reproduced in the framework of the free volume theory of diffusion using a novel procedure based on the use of f h ( T ) as an input experimental parameter.